ROYALTI PENGGUNAAN MEREK DALAM SISTEM FRANCHISE DI INDONESIA MENURUT HUKUM ISLAM - Nasrullah Nasrullah (Al-Adl : Jurnal Hukum, 2021)
Business practices with the Franchise sistem in Indonesia are growing and developing, so we often encounter them around us. This kind of business sistem was basically started and popularized by westerners who incidentally is a capitalist sistem, so that for the Indonesian people, who are predominantly Muslim, this franchise is certainly a business sistem that must be studied in depth according to sharia, because specifically the use of brands must be charged other than fees other. This research is a normative juridical research with library research method. Sources of legal materials in this study include primary legal materials, namely regulations on Franchise, secondary legal materials, namely references in the form of literature related to the Franchise business, then tertiary legal materials such as Indonesian language dictionaries. From the research, it is known that the Franchise sistem applied in Indonesia is a business format franchise sistem, where a Franchisee obtains the right to market and sell products or services in a specific area or location using the operational and marketing standards of the Franchisor. The law of fee royalty for the use of brands in the franchise business sistem follows the law of syirkah which is allowed as long as the business, product or service is not prohibited by Islamic law.